Gaya Komunikasi Generasi Z: Pengaruhnya di Lingkungan Kantor - Fathya Nazwa Uziani Syarifah; Novalinda Imaniyar Cahyana; Harmon Chaniago (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the communication style of Generation Z (Gen Z) in the workplace and its impact on organizational dynamics. Gen Z, born between 1997–2012, grew up in the digital era and brings unique characteristics such as reliance on technology, a preference for flexibility, and a strong need for collaboration and inclusion. This research employs a literature review method with a qualitative approach to synthesize findings from various sources. The results indicate that Gen Z tends to adopt a collaborative communication style (